1969
DOI: 10.1172/jci106117
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of angiotensin in experimental renovascular hypertension: an immunologic approach

Abstract: A B S T R A C T The role of angiotensin in three forms of experimental hypertension was assessed in rats. First, the acute blood pressure response to injected angiotensin amide and angiotensin acid was determined. Rats made hypertensive with deoxycorticosterone and saline showed exaggerated responses; rats made hypertensive by clipping one renal artery showed depressed responses; and rats made hypertensive by clipping one renal artery and contralateral nephrectomy showed normal responsivity to angiotensin amid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

1972
1972
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…8 Furthermore, removal of the clip or ligature is attended by a prompt return of blood pressure to normal that is paralleled by a reduction in PRA and circulating Ang II. 9 In addition, active or passive immunization to Ang II 10 or the administration of renin inhibitors 1 ' can lower blood pressure in 2K1C chronic severe hypertension. The renin inhibitor CGP-29287 caused declines in blood pressure that could be correlated with basal PRA in one study.…”
Section: Various Phases Of Goldblatt Hypertension Phase I or Renin-anmentioning
confidence: 99%
“…8 Furthermore, removal of the clip or ligature is attended by a prompt return of blood pressure to normal that is paralleled by a reduction in PRA and circulating Ang II. 9 In addition, active or passive immunization to Ang II 10 or the administration of renin inhibitors 1 ' can lower blood pressure in 2K1C chronic severe hypertension. The renin inhibitor CGP-29287 caused declines in blood pressure that could be correlated with basal PRA in one study.…”
Section: Various Phases Of Goldblatt Hypertension Phase I or Renin-anmentioning
confidence: 99%
“…Furthermore, DEAE-cellulose chromatography in a descending pH gradient," employed on an Table I. • The ability of these rabbits to respond to an intravenous prcssor dose of renin while their blood pressure was lowered is presented in Table 4. One Gokiblatt unit (GU) of rabbit renin 1 ' was given via the marginal ear vein. Systolic blood pressures were measured in mm Hg at frequent intervals and were plotted against time in minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental parallel, i.e., unilateral renal artery constriction with the opposite kidney untouched, produces hypertension in rats, while other experimental animals usually remain normotensive. Christlieb et al (6) found such hypertension alleviated by immunization with angiotensin, but this could not be confirmed by Johnston et al (5). Whatever the reason for the difference in results, both groups started immunization subsequent to the development of hypertension; neither group investigated whether antibody titers were sufficient for the complete inactivation of 150 EIDE injected angiotensin.'…”
mentioning
confidence: 88%